The Yeast Mating-Type Switching Mechanism: A Memoir - Klar, Amar J. S. (Genetics Society of America, 2010)
It has been 33 years since I first presented results of genetic experiments that established the gene transposition model as the mechanism of mating-type switching in the budding yeast Saccharomyces cerevisiae at the Cold Spring Harbor Laboratory (CSHL) Yeast Genetics meeting in August 1977. Over two decades ago the Genetics Perspectives editors solicited a perspective on my participation in the studies that deciphered the mechanism of mating-type switching and revealed the phenomenon of gene silencing in yeast. Although flattered at the time, I thought that preparation of such an article called for a more seasoned researcher who had benefitted from seeing his contributions stand the test of time. Now realizing that our discovery of the transposition of a mutation from the HMα locus into the MAT (mating type) locus has provided the genetic evidence that established the gene transposition model, and having witnessed our conclusions confirmed by subsequent molecular studies, I decided that perhaps this is a good time to recount the chronology of events as they unfolded for me decades ago.